Application of a management and storage system for knowledge generated from simulation projects as a teaching and assessment tool. (December 2021) - Pereira, Tábata Fernandes; Montevechi, José Arnaldo Barra; Leal, Fabiano; Miranda, Rafael de Carvalho; Scheidegger, Anna Paula Galvão
During the development of a simulation project, people involved in the study acquire greater knowledge of the system being simulated. However, this knowledge is usually not externalized and ends up being lost at the end of the project. In this context, knowledge management allied with information technology may assist in information management and enable the collection, storage, and dissemination of knowledge. Thus, this paper aims to discuss and present a knowledge management system to manage and to store the knowledge generated by analysts in simulation projects. Our intention was to demonstrate a way that the knowledge can be stored and accessed at any moment by anyone to recover the development process and avoid mistakes during a simulation project. In order to achieve this goal, some graduate and undergraduate simulation courses at a Brazilian federal university were used as objects of study. At the end of the study, it was concluded that knowledge management integrated with information technology contributes to the work of simulation analysts by supporting information and knowledge management throughout the stages of the simulation projects.